2018
DOI: 10.1038/s41598-018-32602-z
|View full text |Cite
|
Sign up to set email alerts
|

Sun-induced fluorescence and gross primary productivity during a heat wave

Abstract: Remote sensing of sun-induced chlorophyll fluorescence (SIF) has been suggested as a promising approach for probing changes in global terrestrial gross primary productivity (GPP). To date, however, most studies were conducted in situations when/where changes in both SIF and GPP were driven by large changes in the absorbed photosynthetically active radiation (APAR) and phenology. Here we quantified SIF and GPP during a short-term intense heat wave at a Mediterranean pine forest, during which changes in APAR wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
73
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(82 citation statements)
references
References 62 publications
8
73
1
Order By: Relevance
“…Even though our study indicates a larger uptake of CO 2 across multiple biomes compared to conventional CO 2 flux partitioning, our GPP estimate lies within the uncertainty of the GPP reported in Beer et al () and thus does not support recent reports of substantially higher estimates (Arneth et al, ; Welp et al, ). To take advantage of newly emerging constraints on GPP, for example, COS (Wohlfahrt et al, ), isotopic flux partitioning (Wehr et al, ), and Sun‐induced fluorescence (Wohlfahrt et al, ), should be compared and combined with traditional flux partitioning to understand the differences between methods and to decrease the overall uncertainty of GPP.…”
Section: Discussionmentioning
confidence: 99%
“…Even though our study indicates a larger uptake of CO 2 across multiple biomes compared to conventional CO 2 flux partitioning, our GPP estimate lies within the uncertainty of the GPP reported in Beer et al () and thus does not support recent reports of substantially higher estimates (Arneth et al, ; Welp et al, ). To take advantage of newly emerging constraints on GPP, for example, COS (Wohlfahrt et al, ), isotopic flux partitioning (Wehr et al, ), and Sun‐induced fluorescence (Wohlfahrt et al, ), should be compared and combined with traditional flux partitioning to understand the differences between methods and to decrease the overall uncertainty of GPP.…”
Section: Discussionmentioning
confidence: 99%
“…Walther [79], using SiF retrieved from the GOME-2 instrument, explored the seasonality in SiF in a high latitude evergreen ecosystem, and reported a strong seasonal relationship between satellite SiF and modelled GPP. Furthermore, Wolfhart [39] studied a short time series (10 days in length) of SiF in an evergreen canopy that had experienced a short but intense heatwave, and found that during a short period of unchanging APAR, SiF was only very weakly related to the change in GPP, a change attributed to the fact APAR was almost unchanged during the analysis period. In our study, statistically significant relationships only emerged following filtering to limit analyses to midday, cloud free days with high SZA.…”
Section: Comparison Between Evergreen Forest Sif and Other Terrestriamentioning
confidence: 99%
“…However, recent articles have highlighted, with varying degrees of success, the ability to extract SiF from orbiting platforms (e.g., from the Japanese Greenhouse gases Observing SATellite, GOSAT, and from the Global Ozone Monitoring Experiment-2, GOME-2) for estimating GPP [27,[35][36][37]. These findings highlighted that spatial and temporal patterns of satellite retrieved SiF were highly correlated with GPP at the biome and global levels [33], but such correlations weaken at individual higher temporal and spatial resolutions [38] or during extreme climatic events [39]. Field based studies are continuing to emerge [20,25,29,[40][41][42][43][44] though long term data sets, covering multiple seasons, are still rare [45][46][47].…”
Section: Introductionmentioning
confidence: 97%
“…down to at least 2 m) where soil water content remains fairly constant (Domec et al 2004. Our data indicate that when air temperatures are anomalously high during a dry summer, as in 2015, decreased GPP is further exacerbated by stomatal closure in response to higher VPD and also likely by downregulation of enzymes (Wohlfahrt et al 2018), resulting in substantially lower pWUE. This finding agrees with the wavelet analysis by Wagle et al (2016), which indicates that carbon uptake (NEP or GPP) is constrained more than ET by VPD through restriction of stomatal regulation.…”
Section: Early Growing Seasonmentioning
confidence: 76%